Networked Learning dengan Strategi Problem Solving Pada Mata Pelajaran Simulasi Digital - Maharani Lelasari; Punaji Setyosari; Saida Ulfa (Universitas Negeri Malang, 2019)
Abstract: Limitations of computer laboratory becomes one of the obstacles of the implementation of Digital Simulation learning at Vocational High School level which mostly implemented through practice. Almost every student in the class has a smartphone with good specifications, by utilizing smartphones and laptops as well as internet networks, networked learning can be applied to support learning Digital Simulation of Communication in the Network materials. So that the learning of Digital Simulation can be done well without the  need of computer laboratory namely by training students to communicate directly in the network through the process of solving problems by utilizing SLN Schoology. In developing this networked learning product used Lee & Owens (2004) development model and has been declared by expert and has been declared effective. Abstrak: Keterbatasan laboratorium komputer menjadi salah satu kendala dalam pelaksanaan pembelajaran Simulasi Digital di tingkat Sekolah Menengah Kejuruan yang sebagian besar dilaksanakan melalui praktik. Hampir setiap siswa di kelas memiliki smartphone dengan spesifikasi yang baik, dengan memanfaatkan smartphone dan laptop serta jaringan internet, pembelajaran jaringan dapat diterapkan untuk mendukung pembelajaran Simulasi Digital materi Komunikasi dalam Jaringan. Sehingga pembelajaran dapat dilakukan dengan baik tanpa memerlukan laboratorium komputer yaitu dengan melatih siswa untuk berkomunikasi secara langsung dalam jaringan melalui proses pemecahan masalah. Dalam mengembangkan produk pembelajaran jaringan ini digunakan model pengembangan Lee & Owens (2004) dan telah divalidasi oleh ahli serta dinyatakan efektif.